A polymer-based composite electrolyte and its preparation method and application, lithium-ion battery

By introducing zinc ion compounds into the composite polymer matrix of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene to form a composite structure, the problem of ion conductivity bottleneck of polymer-based composite electrolyte at room temperature is solved, the lithium ion conductivity and interface stability are significantly improved, and the stable cycle time of lithium ion batteries is extended.

CN119742435APending Publication Date: 2025-04-01SHANDONG CHUANGLU ADVANCED BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411896514.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The ionic conductivity of existing polymer-based composite solid electrolytes still has bottlenecks at room temperature, which is unstable to lithium metal, resulting in limited working life.

Method used

By introducing zinc ion compounds into the composite polymer matrix of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene, a composite structure of lithium salt, active filler and zinc ion compound is formed, which promotes the full decomposition of lithium salt and zinc ion compound, and improves lithium ion conductivity and interface stability.

Benefits of technology

The lithium ion conductivity and interface stability of polymer-based composite electrolytes are significantly improved, so that the electrolyte has higher ion transport performance and higher stability to lithium metal at room temperature, and extends the stability cycle time of lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742435A_ABST
    Figure CN119742435A_ABST
Patent Text Reader

Abstract

The present invention provides a polymer-based composite electrolyte and a preparation method and application thereof, and a lithium-ion battery, which belong to the technical field of energy storage materials. The polymer-based composite electrolyte provided by the present invention comprises a composite polymer membrane and a lithium salt, an active filler and a zinc ion compound doped in the composite polymer membrane; the zinc ions in the zinc ion compound, the lithium ions in the lithium salt and the polymer in the composite polymer membrane form a coordination structure; the composite polymer in the composite polymer membrane is polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene. The present invention introduces a zinc ion compound with ion coordination characteristics into the composite polymer matrix, regulates the coordination structure of the lithium salt anion and the polymer matrix, thereby weakening the coordination environment of the lithium ions; it can promote the full decomposition of the lithium salt and the zinc ion compound, form products such as LiF that are beneficial to the interface stability, and improve the lithium ion conductivity and interface stability of the polymer-based composite electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage materials, and specifically relates to a polymer-based composite electrolyte, a preparation method and application thereof, and a lithium-ion battery. Background Art

[0002] With the development of modern science and technology, especially the growing demand for high-performance batteries in the fields of energy, electronics and automobiles, solid electrolyte materials, as a key component of next-generation battery technology, have received widespread attention. Compared with traditional liquid electrolytes, solid electrolytes have better safety, chemical stability and environmental friendliness, and are an important foundation for the development of solid-state battery technology. However, the room temperature performance of solid electrolytes, especially ionic conductivity, is still one of the main obstacles to the widespread application of solid-state batteries.

[0003] At present, the research on solid electrolytes mainly focuses on inorganic materials, polymer materials and composite materials of the two. Inorganic solid electrolytes such as oxides, sulfides and halides have high ionic conductivity, but they are brittle and prone to mechanical damage. The manufacturing process is complex and the cost is high. Polymer-based electrolytes have good flexibility, processability and low cost, but their ionic conductivity is often low, especially at room temperature. Polymer-based electrolytes are usually unstable to lithium metal and are not enough to meet the needs of practical applications.

[0004] In order to solve the above problems, researchers have gradually combined polymers with inorganic materials to develop composite solid electrolytes in recent years. Polymer-based composite solid electrolytes can improve ionic conductivity to a certain extent by introducing inorganic ion conductor materials while maintaining the processability and flexibility of the polymer. However, the ionic conductivity of existing polymer-based composite solid electrolytes at room temperature still has certain bottlenecks, and their instability to lithium metal leads to a limited working life. Summary of the invention

[0005] The purpose of the present invention is to provide a polymer-based composite electrolyte and a preparation method and application thereof, and a lithium-ion battery. The polymer-based composite electrolyte provided by the present invention has high ionic conductivity and high stability to lithium metal.

[0006] In order to achieve the purpose of the present invention, the present invention provides the following technical solutions:

[0007] A polymer-based composite electrolyte comprises a composite polymer membrane and a lithium salt, an active filler and a zinc ion compound doped in the composite polymer membrane; zinc ions in the zinc ion compound, lithium ions in the lithium salt and a polymer in the composite polymer membrane form a coordination structure;

[0008] The composite polymer in the composite polymer film is polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene; the mass ratio of polyethylene oxide to polyvinylidene fluoride-hexafluoropropylene is 4-24:1.

[0009] Preferably, the zinc ion compound includes one or more of zinc sulfonate, inorganic acid zinc salt, zinc phthalocyanine, zinc tetraphenylporphyrin and zinc phytate.

[0010] Preferably, the lithium salt includes one or more of a fluorine-containing inorganic anion lithium salt, a fluorine-free inorganic anion lithium salt and an organic anion lithium salt.

[0011] Preferably, the active filler includes one or more of a garnet-type solid electrolyte, a phosphate-type solid electrolyte, a sulfide solid electrolyte, a lithium phosphorus oxynitride and an inorganic chloride electrolyte.

[0012] Preferably, the mass of the zinc ion compound accounts for 1 to 40% of the mass of the composite polymer;

[0013] The molar ratio of EO in the polyethylene oxide to Li in the lithium salt is 2 to 45:1;

[0014] The mass of the active filler accounts for 1 to 60% of the mass of the composite polymer.

[0015] The present invention also provides a method for preparing the polymer-based composite electrolyte described in the above technical solution, comprising the following steps:

[0016] The composite polymer, lithium salt, active filler, zinc ion compound and organic solvent are mixed, molded and dried to obtain the polymer-based composite electrolyte.

[0017] Preferably, the organic solvent comprises one or more of acetonitrile, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide.

[0018] Preferably, the mixing temperature is 30 to 100° C. and the mixing time is 6 to 48 hours;

[0019] The drying temperature is 40-100° C. and the drying time is 5-72 hours.

[0020] The present invention also provides the use of the polymer-based composite electrolyte described in the above technical solution or the polymer-based composite electrolyte prepared by the preparation method described in the above technical solution in a lithium-ion battery.

[0021] The present invention also provides a lithium ion battery, comprising a positive electrode, an electrolyte and a negative electrode, wherein the electrolyte is the polymer-based composite electrolyte described in the above technical solution or the polymer-based composite electrolyte prepared by the preparation method described in the above technical solution.

[0022] The invention provides a polymer-based composite electrolyte, comprising a composite polymer membrane and a lithium salt, an active filler and a zinc ion compound doped in the composite polymer membrane; the zinc ions in the zinc ion compound, the lithium ions in the lithium salt and the polymer in the composite polymer membrane form a coordination structure; the composite polymer in the composite polymer membrane is polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene; the mass ratio of polyethylene oxide to polyvinylidene fluoride-hexafluoropropylene is 4 to 24:1. The invention uses polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene as polymer matrices, and has excellent film-forming properties and interface properties. In addition, a zinc ion compound with ion coordination characteristics is introduced into the composite polymer matrix of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene to promote the coordination structure of lithium salt anions and the polymer matrix, thereby weakening the coordination environment of lithium ions. The coordination structure formed by zinc ions and polymers between the interface of lithium metal and solid electrolyte can promote the full decomposition of lithium salt and zinc ion compounds, not only forming products such as LiF that are beneficial to interface stability, but also increasing the active lithium content in the polymer, while reducing the crystallinity of the polymer, thereby improving the lithium ion conductivity and interface stability of the polymer-based composite electrolyte, so that the electrolyte has higher ion transmission performance and higher stability to lithium metal at room temperature.

[0023] Furthermore, the present invention adjusts the lithium ion conductivity and interface stability by controlling the amounts of polyethylene oxide (PEO), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), lithium salt, active filler and zinc ion compound, so that the polymer-based polymer solid electrolyte provided by the present invention has higher lithium ion conductivity and can greatly improve the stable cycle time of the lithium ion symmetric battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 The lithium ion conductivity diagram of the polymer-based composite solid electrolyte obtained in Example 1;

[0026] Figure 2 This is a test diagram of the cycle performance of a lithium symmetric half-cell assembled with the electrolyte obtained in Example 1;

[0027] Figure 3 This is a graph of lithium ion conductivity of the polymer-based composite solid electrolyte obtained in Example 2;

[0028] Figure 4This is a test diagram of the cycle performance of a lithium symmetric half-cell assembled with the electrolyte obtained in Example 2;

[0029] Figure 5 This is a graph of lithium ion conductivity of the polymer-based composite solid electrolyte obtained in Example 3;

[0030] Figure 6 This is a test diagram of the cycle performance of a lithium symmetric half-cell assembled with the electrolyte obtained in Example 3;

[0031] Figure 7 This is a graph of lithium ion conductivity of the polymer-based composite solid electrolyte obtained in Example 4;

[0032] Figure 8 This is a test diagram of the cycle performance of a lithium symmetric half-cell assembled with the electrolyte obtained in Example 4;

[0033] Fig. 9 This is a graph of lithium ion conductivity of the polymer-based composite solid electrolyte obtained in Example 5;

[0034] Fig.10 This is a test diagram of the cycle performance of a lithium symmetric half-cell assembled with the electrolyte obtained in Example 5;

[0035] Fig.11 This is a graph of lithium ion conductivity of the polymer-based composite solid electrolyte obtained in Example 6;

[0036] Fig.12 This is a test diagram of the cycle performance of a lithium symmetric half-cell assembled with the electrolyte obtained in Example 6;

[0037] Fig.13 The lithium ion conductivity diagram of the polymer-based composite electrolyte obtained in Comparative Example 1;

[0038] Fig.14 This is a test diagram of the cycle performance of a lithium symmetric half-cell assembled with the electrolyte obtained in Comparative Example 1;

[0039] Fig.15 The lithium ion conductivity diagram of the polymer-based composite electrolyte obtained in Comparative Example 2;

[0040] Fig.16 This is a test diagram of the cycle performance of a lithium symmetric half-cell assembled with the electrolyte obtained in Comparative Example 2;

[0041] Fig.17 This is the lithium ion conductivity diagram of the polymer-based composite electrolyte obtained in Comparative Example 3. DETAILED DESCRIPTION

[0042] The present invention provides a polymer-based composite electrolyte, comprising a composite polymer membrane and a lithium salt, an active filler and a zinc ion compound doped in the composite polymer membrane; the zinc ions in the zinc ion compound, the lithium ions in the lithium salt and the polymer in the composite polymer membrane form a coordination structure;

[0043] The composite polymer in the composite polymer film is polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene; the mass ratio of polyethylene oxide to polyvinylidene fluoride-hexafluoropropylene is 4-24:1.

[0044] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0045] In the present invention, the composite polymer in the composite polymer film is polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene; the mass ratio of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene is 4 to 24:1, and in a specific embodiment, it can be 4:1, 8:1, 12:1, 18:1 or 24:1.

[0046] In the present invention, the number average molecular weight of the polyethylene oxide is 400000 to 600000; the number average / weight average molecular weight of the polyvinylidene fluoride-hexafluoropropylene is 455000 to 650000. The present invention uses polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene as polymer matrices and has excellent film-forming properties and interface properties.

[0047] In the present invention, the lithium salt includes one or more of a fluorine-containing inorganic anion lithium salt, a fluorine-free inorganic anion lithium salt and an organic anion lithium salt; the fluorine-containing inorganic anion lithium salt is one of bis(fluorosulfonyl)imide lithium salt (LiFSI), lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4) and lithium difluorophosphate (LiPO2F2), and in a specific embodiment, it can be LiTFSI; the fluorine-free inorganic anion lithium salt is lithium bis(oxalate)borate (LiBOB) or lithium perchlorate (LiClO4); the organic anion lithium salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium difluorooxalateborate (LiDFOB) or lithium trifluoromethanesulfonate (LiOTF). In the present invention, the lithium salt has the functions of providing conductive ions, transmitting lithium ions and maintaining the balance of battery reactions.

[0048] In the present invention, the molar ratio of EO in the polyethylene oxide to Li in the lithium salt is 2 to 45:1. In specific embodiments, it can be 4:1, 10:1, 15:1, 24:1 or 30:1.

[0049] In the present invention, the active filler includes one or more of a garnet-type solid electrolyte, a phosphate-type solid electrolyte, a sulfide solid electrolyte, lithium phosphorus oxynitride (LiPON) and an inorganic chloride electrolyte; the garnet-type solid electrolyte is LLZO or LLZTO, and in a specific embodiment, it can be LLZTO; the phosphate-type solid electrolyte is LATP; the sulfide solid electrolyte includes LPSC or LGPS. In the present invention, the active filler can reduce the crystallinity of the polymer and promote the transfer of electrons / conductive ions, and has the effect of improving ionic conductivity.

[0050] In the present invention, the mass of the active filler accounts for 1-60% of the mass of the composite polymer. In specific embodiments, it can be 5%, 8%, 10%, 12%, 20%, 30%, 45% or 50%.

[0051] In the present invention, the zinc ion compound includes one or more of a sulfonate zinc compound, an inorganic acid zinc compound, zinc phthalocyanine, tetraphenylporphyrin zinc and phytic acid zinc; the sulfonate zinc compound is one of zinc trifluoromethanesulfonate, zinc difluoromethanesulfinic acid and zinc isopropylsulfinic acid; the inorganic acid zinc compound is zinc perchlorate or zinc tetrafluoroborate, and in a specific embodiment, it can be zinc perchlorate. The present invention introduces a zinc ion compound with ion coordination characteristics to regulate the coordination structure of lithium salt anions and polymer matrix, thereby weakening the coordination environment of lithium ions; this coordination structure at the interface promotes the full decomposition of lithium salts and zinc ion compounds, forming products such as LiF that are beneficial to interface stability, improving the lithium ion conductivity and interface stability of the polymer-based composite electrolyte, so that the electrolyte has higher ion transport performance and higher stability to lithium metal at room temperature.

[0052] In the present invention, the mass of the zinc ion compound accounts for 1-40% of the mass of the composite polymer. In specific embodiments, it can be 10%, 12%, 20%, 25% or 32%.

[0053] The present invention also provides a method for preparing the polymer-based composite electrolyte described in the above technical solution, comprising the following steps:

[0054] The raw materials for preparing the polymer-based composite electrolyte and the organic solvent are mixed, and the mixture is shaped and dried to obtain the polymer-based composite electrolyte.

[0055] In the present invention, the organic solvent includes one or more of acetonitrile, N,N-dimethylacetamide (DMAC), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP) and N,N-dimethylformamide (DMF).

[0056] In the present invention, the lithium salt and the organic solvent are first mixed, and then the zinc ion compound, the active filler and the composite polymer are added in sequence for the second mixing, and the polymer-based composite electrolyte is obtained after drying; the temperature of the first mixing is room temperature; the first mixing is carried out under stirring conditions; the stirring frequency is 100-600rpm / min, and in a specific embodiment, it can be 220, 250, 360 or 500rpm / min; the present invention has no special restrictions on the time of the first mixing, and the raw materials can be completely dissolved or mixed uniformly. In the present invention, the temperature of the second mixing is 30-100°C, and in a specific embodiment, it can be 45, 60 or 80°C; the time is 6-48h, and in a specific embodiment, it can be 10, 12, 24h or 40h; the second mixing is carried out under stirring conditions; the stirring frequency is 100-600rpm / min, and in a specific embodiment, it can be 200, 300 or 400rpm / min.

[0057] In the present invention, the polyethylene oxide (PEO) is dried before use; the drying temperature is 30 to 120° C., and in a specific embodiment, it can be 45 or 60° C.; the drying time is 8 to 30 hours, and in a specific embodiment, it can be 10 or 20 hours.

[0058] In the present invention, the drying is vacuum drying; the drying temperature is 40-100°C, and in a specific embodiment, it can be 50, 70 or 80°C; the drying time is 5-72h, and in a specific embodiment, it can be 10, 12, 20 or 36h.

[0059] The present invention also provides the use of the polymer-based composite electrolyte described in the above technical solution or the polymer-based composite electrolyte prepared by the preparation method described in the above technical solution in a lithium-ion battery.

[0060] In the present invention, the lithium-ion battery is an all-solid-state lithium metal battery.

[0061] The present invention also provides a lithium ion battery, comprising a positive electrode, an electrolyte and a negative electrode, wherein the electrolyte is the polymer-based composite electrolyte described in the above technical solution or the polymer-based composite electrolyte prepared by the preparation method described in the above technical solution.

[0062] In order to further illustrate the present invention, the polymer-based composite electrolyte, preparation method and application thereof, and lithium-ion battery provided by the present invention are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0063] Example 1

[0064] Weigh 2.4 g PEO and 0.1 g PVDF-HFP for later use;

[0065] According to EO and Li + The molar ratio of LiTFSI is 24:1. LiTFSI is weighed and dissolved in acetonitrile solvent. The mixture is stirred at 250 rpm / min at room temperature for 10 min. Then 0.5 g zinc perchlorate is added and stirred for another 10 min. After the zinc perchlorate is completely dissolved, 0.5 g LLZTO is added and stirred continuously at 250 r / min. 2.4 g PEO and 0.1 g PVDF-HFP are slowly dispersed and dissolved in the mixed solution respectively. After the dispersion is complete, stir at 200 r / min for 24 h at 60 ° C to obtain a uniform slurry. The slurry is vacuum dried at 80 ° C for 36 h to obtain a polymer-based composite solid electrolyte.

[0066] Example 2

[0067] Weigh 1.8 g PEO and 0.1 g PVDF-HFP and set aside;

[0068] According to EO and Li + The molar ratio of LiTFSI is 20:1. LiTFSI is weighed and dissolved in DMF solvent. The mixture is stirred at 250 rpm / min at room temperature for 8 minutes. Then 0.285 g of zinc trifluoromethanesulfonate is added and stirred for 6 minutes. After the zinc trifluoromethanesulfonate is dissolved, 0.285 g of LLZTO is added and stirred at 320 r / min. 1.8 g of PEO and 0.1 g of PVDF-HFP are slowly dispersed and dissolved in the mixed solution respectively. After the dispersion is complete, the mixture is stirred at 310 r / min at 100 ° C for 6 hours to obtain a uniform slurry. The mixture is vacuum dried at 80 ° C for 36 hours to obtain a polymer-based composite solid electrolyte.

[0069] Example 3

[0070] Weigh 1.2 g PEO and 0.1 g PVDF-HFP and set aside;

[0071] According to EO and Li + The molar ratio of LiTFSI is 15:1. LiTFSI is weighed and dissolved in NMP solvent. The mixture is stirred at 360 rpm / min at room temperature for 45 min. Then 0.156 g of zinc difluoromethanesulfinate is added and stirred for 15 min. After the zinc difluoromethanesulfinate is dissolved, 0.156 g of LLZTO is added and stirred at 320 r / min. 1.2 g of PEO and 0.1 g of PVDF-HFP are slowly dispersed and dissolved in the mixed solution respectively. After the dispersion is complete, stir at 350 r / min for 20 h at 80 ° C to obtain a uniform slurry. The slurry is vacuum dried at 80 ° C for 36 h to obtain a polymer-based composite solid electrolyte.

[0072] Example 4

[0073] Weigh 0.8 g PEO and 0.1 g PVDF-HFP for later use;

[0074] According to EO and Li + The molar ratio of LiTFSI is 10:1. LiTFSI is weighed and dissolved in DMSO solvent. The mixture is stirred at 220 rpm / min at room temperature for 60 min. Then 0.09 g of zinc tetrafluoroborate is added and stirred for 25 min. After the zinc tetrafluoroborate is dissolved, 0.072 g of LLZTO is added and stirred at 420 r / min. 0.8 g of PEO and 0.1 g of PVDF-HFP are slowly dispersed and dissolved in the mixed solution respectively. After the dispersion is complete, stir at 400 r / min for 12 h at 45 ° C to obtain a uniform slurry. The slurry is vacuum dried at 80 ° C for 36 h to obtain a polymer-based composite solid electrolyte.

[0075] Example 5

[0076] Weigh 0.5 g PEO and 0.1 g PVDF-HFP for later use;

[0077] According to EO and Li + The molar ratio of LiTFSI is 4:1. LiTFSI is weighed and dissolved in DMAC solvent. The mixture is stirred at 500 rpm / min at room temperature for 20 min. Then 0.072 g of zinc isopropylsulfinate is added and stirred for 50 min. After the zinc isopropylsulfinate is dissolved, 0.03 g of LLZTO is added and stirred at 300 r / min. 0.5 g of PEO and 0.1 g of PVDF-HFP are slowly dispersed and dissolved in the mixed solution respectively. After the dispersion is complete, stir at 350 r / min for 40 h at 30 ° C to obtain a uniform slurry. The slurry is vacuum dried at 80 ° C for 36 h to obtain a polymer-based composite solid electrolyte.

[0078] Example 6

[0079] Weigh 1.6 g PEO and 0.4 g PVDF-HFP for later use;

[0080] According to EO and Li +The molar ratio of LiTFSI is 12:1. LiTFSI is weighed and dissolved in DMF solvent. The mixture is stirred at 250 rpm / min for 10 min at room temperature. Then 0.2 g of zinc phytate is added and stirred for another 10 min. After the zinc phytate is dissolved, 0.2 g of LLZTO is added and stirred continuously at 250 r / min. 1.4 g of PEO and 0.4 g of PVDF-HFP are slowly dispersed and dissolved in the mixed solution respectively. After the dispersion is complete, stir at 200 r / min for 24 h at 60 ° C to obtain a uniform slurry. The slurry is vacuum dried at 80 ° C for 36 h to obtain a polymer-based composite solid electrolyte.

[0081] Comparative Example 1

[0082] Weigh 1.6 g PEO and 0.4 g PVDF761 for later use;

[0083] According to EO and Li + The molar ratio of LiTFSI is 12:1. LiTFSI is weighed and dissolved in DMAC solvent. The mixture is stirred at 250 rpm / min for 10 min at room temperature. Then 0.2 g of zinc phthalocyanine is added and stirred for another 10 min. After the zinc phthalocyanine is dissolved, 0.2 g of LLZTO is added and stirred continuously at 250 r / min. 1.6 g of PEO and 0.4 g of PVDF-HFP are slowly dispersed and dissolved in the mixed solution respectively. After the dispersion is complete, the mixture is stirred at 200 r / min for 24 h at 60 ° C to obtain a polymer-based composite electrolyte slurry. The mixture is vacuum dried at 80 ° C for 36 h to obtain a polymer-based composite solid electrolyte.

[0084] Comparative Example 2

[0085] Weigh 1.6 g PEO and 0.4 g PVDF761 for later use;

[0086] According to EO and Li + The molar ratio of LiTFSI is 12:1. LiTFSI is weighed and dissolved in DMAC solvent. The mixture is stirred at 250 rpm / min for 10 min at room temperature. 0.2 g of LATP doped with Zn is added and stirred continuously at 250 r / min. 1.6 g of PEO and 0.4 g of PVDF-HFP are slowly dispersed and dissolved in the mixed solution respectively. After the dispersion is complete, the mixture is stirred at 200 r / min for 24 h at 60 ° C to obtain a polymer-based composite electrolyte slurry. The mixture is vacuum dried at 80 ° C for 36 h to obtain a polymer-based composite solid electrolyte.

[0087] Comparative Example 3

[0088] Weigh 1.6 g PEO and 0.4 g PVDF761 for later use;

[0089] According to EO and Li + The molar ratio of LiTFSI is 12:1. LiTFSI is weighed and dissolved in DMF solvent. The mixture is stirred at 300 rpm / min at room temperature for 25 minutes. Then 0.25 g of zinc phthalocyanine is added and stirred for 10 minutes. After the zinc phthalocyanine is dissolved, 0.25 g of LLZTO is added and stirred at 300 r / min. 1.6 g of PEO and 0.4 g of PVDF are slowly dispersed and dissolved in the mixed solution respectively. After the dispersion is complete, stir at 350 r / min for 18 hours at 75 ° C to obtain a polymer-based composite electrolyte slurry. The slurry is vacuum dried at 75 ° C for 30 hours to obtain a polymer-based composite solid electrolyte.

[0090] Test Case

[0091] The polymer-based composite electrolytes obtained in Examples 1 to 6 and Comparative Examples 1 to 3 were assembled into lithium symmetric half-cells. -1 The stable cyclability of the lithium battery obtained by current density test is shown below.

[0092] Table 1 Performance test results of polymer-based composite electrolytes obtained in Examples 1 to 6 and Comparative Examples 1 to 3

[0093]

[0094] Figures 1 to 17 The lithium ion conductivity diagrams of the polymer-based composite electrolytes obtained in Examples 1 to 6 and Comparative Examples 1 to 3 and the cycle performance test diagrams of the assembled lithium symmetric half-cells are shown in Table 1 and Figures 1 to 17 It can be seen that the polymer-based solid electrolyte provided by the present invention has a high lithium ion conductivity and can greatly improve the symmetrical battery at 0.1 mA·cm -1 The time for stable cycling at a given current density.

[0095] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A polymer-based composite electrolyte, characterized in that: It comprises a composite polymer membrane and a lithium salt, an active filler and a zinc ion compound doped in the composite polymer membrane; the zinc ions in the zinc ion compound, the lithium ions in the lithium salt and the polymer in the composite polymer membrane form a coordination structure; The composite polymer in the composite polymer film is polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene; the mass ratio of polyethylene oxide to polyvinylidene fluoride-hexafluoropropylene is 4-24:

1.

2. The polymer-based composite electrolyte according to claim 1, characterized in that: The zinc ion compound includes one or more of zinc sulfonate, inorganic acid zinc salt, zinc phthalocyanine, tetraphenylporphyrin zinc and zinc phytate.

3. The polymer-based composite electrolyte according to claim 1, characterized in that: The lithium salt includes one or more of a fluorine-containing inorganic anion lithium salt, a fluorine-free inorganic anion lithium salt and an organic anion lithium salt.

4. The polymer-based composite electrolyte according to claim 1, characterized in that: The active filler includes one or more of a garnet-type solid electrolyte, a phosphate-type solid electrolyte, a sulfide solid electrolyte, a lithium phosphorus oxynitride and an inorganic chloride electrolyte.

5. The polymer-based composite electrolyte according to any one of claims 1 to 4, characterized in that: The mass of the zinc ion compound accounts for 1 to 40% of the mass of the composite polymer; The molar ratio of EO in the polyethylene oxide to Li in the lithium salt is 2 to 45:1; The mass of the active filler accounts for 1 to 60% of the mass of the composite polymer.

6. The method for preparing the polymer-based composite electrolyte according to any one of claims 1 to 5, comprising the following steps: The composite polymer, lithium salt, active filler, zinc ion compound and organic solvent are mixed, molded and dried to obtain the polymer-based composite electrolyte.

7. The preparation method according to claim 6, characterized in that: The organic solvent includes one or more of acetonitrile, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide.

8. The preparation method according to claim 6, characterized in that: The mixing temperature is 30 to 100° C. and the mixing time is 6 to 48 hours; The drying temperature is 40-100° C. and the drying time is 5-72 hours.

9. Use of the polymer-based composite electrolyte according to any one of claims 1 to 5 or the polymer-based composite electrolyte prepared by the preparation method according to any one of claims 6 to 8 in lithium-ion batteries.

10. A lithium ion battery comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The electrolyte is the polymer-based composite electrolyte described in any one of claims 1 to 5 or the polymer-based composite electrolyte prepared by the preparation method described in any one of claims 6 to 8.